Initial growth of curauá and paricá under the application of curauá’s vegetal extract - Cordeiro, Iracema Maria; Schwartz, Gustavo; Ferreira, Gracialda Costa; Lameira, Osmar Alves (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
This study had the objective to test the effect of soil fertilization with curauá’s vegetal extract (Ananas erectifolius) over the growth of individuals of curauá and paricá (Schizolobium parahyba var. amazonicum) planted in consortium. The work was carried out in the experimental field of the company Tramontina Belém, municipality of Aurora do Pará, PA, Brazil. The experiment followed a fully randomized experimental design, with five treatments and four repetitions per treatment, totaling 20 experimental plots. The adopted planting spacing was 4 x 3 m among individuals of paricá and 0.80 m x 0.80 m among plants of curauá. The five treatments consisted in different concentrations of curauá’s vegetal extract: 100% extract; 75% extract and 25% water; (3) 50% extract and 50% water; (4) 25% extract and 75% water and (5) a control with 100% water. The curauá’s vegetal extract was applied in a monthly basis during six months and the assessed variables were: number and length of curauá’s leaves and height and diameter of paricá. From the results obtained, it is possible to observe that there was a positive effect of soil fertilization when the curauá’s vegetal extract was used in the concentration of 25% over the number and length of curauá’s leaves, as well as it is possible to infer that positive results occurred in the concentration of 75% over growth in height and diameter of paricá. The curauá’s vegetal extract can be used as organic fertilizer in consortium plantings, however studies in more detail are necessary to permit indications of more efficient concentrations for the growth of individuals of curauá and paricá.